1992
DOI: 10.1111/j.1471-0528.1992.tb13790.x
|View full text |Cite
|
Sign up to set email alerts
|

The cytological detection of persistent cervical intraepithelial neoplasia after local ablative treatment: a comparison of sampling devices

Abstract: Objective To determine whether the cytological detection of persistent cervical intraepithelial neoplasia (CIN) after local ablative treatment is improved by the use of sampling devices other than the Ayre's spatula. Design A randomized controlled study. Setting Lothian Area Colposcopy Clinic. Subjects 856 patients who had received local therapy (CO2 laser or cold coagulation) for CIN II or III between 9 and 30 months earlier. Intervention Each patient had three consecutive cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
2
5
1
Order By: Relevance
“…None of the cases of CIN in breast cancer patients was detected by cervical cytology, although the smears were taken under optimal conditions at colposcopy. This is a worrying finding but is consistent with our previous data (Hughes et al, 1989;Hughes et al, 1992) and with that of other authors (Richart & Barron, 1981;Giles et al, 1988). Giles et al (1988) report a cytological false negative rate of 58% for small lesions of CIN 1 and CIN 2 and postulate that this is due to the failure of these smaller lesions to exfoliate sufficient abnormal cells to enable accurate detection by cytology.…”
Section: Resultssupporting
confidence: 80%
“…None of the cases of CIN in breast cancer patients was detected by cervical cytology, although the smears were taken under optimal conditions at colposcopy. This is a worrying finding but is consistent with our previous data (Hughes et al, 1989;Hughes et al, 1992) and with that of other authors (Richart & Barron, 1981;Giles et al, 1988). Giles et al (1988) report a cytological false negative rate of 58% for small lesions of CIN 1 and CIN 2 and postulate that this is due to the failure of these smaller lesions to exfoliate sufficient abnormal cells to enable accurate detection by cytology.…”
Section: Resultssupporting
confidence: 80%
“…1984) and our data would support this assertion. We found the Multispatula to be significantly better than the Ayre's spatula in this respect, with 76% of Multispatula samples from patients with treated cervical intraepithelial neoplasia (CIN) containing endocervical cells versus 47% of Ayre's samples (Hughes et al 1992). These figures are remarkably similar to those quoted by Pistofidis et al (1984), in relation to antenatal patients, who reported that 81 % of Multispatula…”
Section: Authors' Replysupporting
confidence: 80%
“…In total, the 13 papers described the efficacy of cold coagulation as observed among 4569 women with CIN1‐3 . The remaining nine studies were not included in the meta‐analyses for the following reasons: cold coagulation was provided in combination with another treatment method ( n = 2); treatment was for non‐CIN cervical anomalies ( n = 1); data corresponded to safety/acceptability rather than efficacy ( n = 2); and insufficient data were provided for calculation of cure rates ( n = 4) …”
Section: Resultsmentioning
confidence: 99%
“…Over a median follow‐up period of 81 months, 1.2% displayed recurrent disease. Hughes and colleagues assessed persistence in 856 CIN2‐3 patients treated by either CO 2 laser, or cold coagulation . A total of 130 patients (15%) presented with persistent CIN over 9–30 months’ follow up.…”
Section: Discussionmentioning
confidence: 99%